2014
DOI: 10.5539/elt.v7n8p53
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Direct and Indirect Corrective Feedback on Iranian EFL Learners’ Spelling Errors

Abstract: The aim of the current study was to investigate the impact of indirect corrective feedback on promoting Iranian high school students' spelling accuracy in English (as a foreign language). It compared the effect of direct feedback with indirect feedback on students' written work dictated by their teacher from Chicken Soup for the Mother and Daughter Soul. The study was conducted at the gifted girls' high school in Saveh, Iran. A sample of 56 high school sophomores was randomly assigned to two equal groups of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
3
13
2
1
Order By: Relevance
“…The problem-solving atmosphere experienced by the students accompanied by the guided learning practices provided by the instructor led to the fruitful results attained. The current result agreed with that of (Eslami, 2014;Ferris, & Roberts, 2001; Ghandi, & Journal of Research in Curriculum, Instruction and Educational Technology Maghsoudi, 2014& Hosseiny, 2014Tan & Manochphinyo, 2017). Another conceivable explanation of the result attained is that indirect error correction induced the learners to become more self-activated and responsible for their learning process.…”
Section: Discussionsupporting
confidence: 89%
“…The problem-solving atmosphere experienced by the students accompanied by the guided learning practices provided by the instructor led to the fruitful results attained. The current result agreed with that of (Eslami, 2014;Ferris, & Roberts, 2001; Ghandi, & Journal of Research in Curriculum, Instruction and Educational Technology Maghsoudi, 2014& Hosseiny, 2014Tan & Manochphinyo, 2017). Another conceivable explanation of the result attained is that indirect error correction induced the learners to become more self-activated and responsible for their learning process.…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, most studies which examine the efficiency of indirect feedback towards grammatical accuracy merely focus on mechanical errors (e.g. Baleghizadeh & Dadashi, 2012;Ghandi & Maghsoudi, 2014) and morphological errors (e.g. Varnosfadrani & Ansari, 2011) but did not analyse semantic errors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although peer interaction provided learners with more opportunities for production practice, CF sharpened learners' awareness of their errors which was beneficial for language development. Finally, Ghandi and Maghsoudi (2014) investigated the effect of direct and indirect corrective feedback on enhancing Iranian EFL high school students' spelling accuracy during a five-week period. Statistical analysis showed that indirect feedback promoted students' spelling errors more effectively than direct feedback.…”
Section: Literaturementioning
confidence: 99%